PENGARUH KADAR BIJI PECAH DALAM PENYANGRAIAN TERHADAP CITARASA KOPI ROBUSTA DESA PUCAK SARI, BULELENG, BALI - Puspa Rini, Ayu Indah; Wiranatha, A.A.P Agung Suryawan; Sedana Yoga, I Wayan Gd. (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2017)
The objectives of the research entitled "The Effect of broken coffee beans in Roasting on Taste of Robusta Coffee at Pucak Sari Village, Buleleng, Bali" were  (1) to know the influence of broken beans content of coffee and level of roasting on taste of coffee and (2) to know the level of broken beans and the appropriate level of roasting to produce good coffee taste from Robusta coffee at Pucak Sari Village, Busung Biu Subdistrict, Buleleng Regency. This study used a Randomized Block Design with 15 treatments consisting of 3 levels of roasting namely light, medium and dark and 5 combinations of broken beans content with 10% (10 broken beans: 90 whole beans), 20% (20 broken beans: 80 whole beans), 30% (30 broken beans: 70 wholes beans), 100% broken beans and 100% wholes beans. The research results showed that Pucak Sari robusta coffee on all treatments meet the quality requirements of SNI 01-3542-2004 with water content varying between 2.44% b/b – 3.13% b/b, ash content varying between 4.58% - 4.77%, and the sari content varying betweeen 25.86% w/w – 29.24% w/w. During roasting the coffee beans with high levels of broken beans  produces coffee taste that is not appropriate. The treatment that produces the best coffee taste in Robusta Pucak sari coffee on the result of assessment fragrance, flavor, aftertaste, salt/acid, bitter/sweet, mouthfeel, balance and uniform cup was the treatment of 10% broken beans content (10 broken beans: 90 whole beans) and light roasting (190°C - 195°C).   Keywords: coffee powder, broken beans, robusta coffee, roasting